Changes in Great Plains Low‐Level Jet Structure and Associated Precipitation Over the 20th Century. Issue 3 (3rd February 2022) - Ferguson, Craig R.
Abstract: The U.S. Great Plains warm season climate is inextricably linked to the frequency and structure of the region's southerly low‐level jet. In the present‐day climate (1977–2009), low‐level jets are shown to occur on 26%, 46%, and 62% of May–September days in the northern (NGP), central (CGP) and southern (SGP) Great Plains, respectively, and account for at least 26%, 25%, and 36% of those region's precipitation during the same period. A shortcoming of previous research has been a failure to treat upper‐level dynamically coupled, or cyclone‐induced jets, separately from jets that are relatively uncoupled from synoptic flow. Differentiating between jet types is essential to proper mechanistic diagnosis and attribution of jet‐related wind, precipitation, and temperature changes to their local land or remote oceanic forcing. Using a new CERA‐20C objective dynamical jet classification dataset, this study achieves the first quantitative assessment of changes in coupled and uncoupled jets between 1901 and 2010 for NGP, CGP, and SGP. Declines in warm season jet frequency are pinpointed to July–September jets. In the NGP and CGP, both jet types have undergone significant increases in speed and height with concomitant decreases in CAPE and precipitation. NGP uncoupled jet and CGP coupled jet precipitation has decreased by 0.5 and 0.8 mm day −1, respectively, which accounts for 41%–44% of total May–September precipitation decreases between 1905–1937 and 1977–2009. A dynamic situation in which synoptic and local soil moisture changes drive opposite jet responses is discussed. Key Points: Great Plains low‐level jets have decreased in frequency but increased in strength over the past century Decreases in jet precipitation explains 41%–44% of present‐day May–September precipitation shortfalls relative to 1905–1937 norms Intensification of Pacific and Atlantic subtropical highs and enhanced Rockies ridging opposes localized drying in the jet response